Susceptibility measurements from the neolithic settlement Wanna 1603, Ldkr. Cux., Germany - Mennenga, Moritz; Frederiks, Pière Leon (Niedersächsisches Institut für historische Küstenforschung, Wilhelmshaven, 2023)
The samples examined were taken in the run-up to the sondage of a Neolithic settlement site under the bog near Wanna, district Cuxhaven, Germany. In order to determine the extent of the cultural layer, susceptibility measurements were taken on the mineral sediment under the peat. The measurements had to be made in the laboratory and were carried out with a Bartington MS3 and MS2B.
Keywords: archaeology; susceptibility